Effects of Zinc Fertilization on Various Mungbean Cultivars in the Madhupur Tract of Bangladesh - Ahammad, Tanvir; Islam, Most Zakiya; Islam, Mohammed Ariful; Habib, Marzia; Hossain, Md Ashraf; Khan, Md Sirajul Islam (Journal of the Bangladesh Agricultural University, 2025)
Mungbean (Vigna radiata) is cultivated globally for its high protein content, yet its production remains limited due to zinc (Zn) deficiency in the soil. An experiment was performed to evaluate the response of different mungbean varieties to zinc fertilization. The treatments included two levels of zinc fertilization (0 and 2 kg ha⁻¹), and five mungbean varieties BARI Mung-4, BARI Mung-5, BARI Mung-6, BARI Mung-7, and BARI Mung-8. The research was laid out using a randomized complete block design (RCBD) with three replications. BARI Mung-6 exhibited the highest values for number of pods per plant (27.33), pod length (9.40 cm), seed yield (988.80 kg ha⁻¹), 100-seed weight (4.88 g), stover yield (2361.70 kg ha⁻¹), and biological yield (3350.50 kg ha⁻¹) over other tested varieties. Zinc fertilization increased by 9.845% in plant height, 8.045% of the number of pods plant-1, 3.448% number of seeds pod-1, 3.209% pod length, and 7.124% in the 100-seed weight compared to the control. The maximum 100-seed weight (5.06 g), seed yield (1044.00 kg ha⁻¹), number of pods per plant (29.00), pod length (9.50 cm), stover yield (2483.30 kg ha⁻¹), and biological yield (3527.30 kg ha⁻¹) were achieved in BARI Mung-6 fertilized with 2.0 kg Zn ha⁻¹ among all treatment combinations. Additionally, the BARI Mung-6 fertilized with zine superior concentrations of potassium (K), zinc (Zn), and boron (B) in both seed and stover, though phosphorus (P) and sulfur (S) concentrations did not vary significantly. J Bangladesh Agril Univ 23(1): 9–17, 2025